THE SPILLOVER OF THE COFFEE: MATERIAL MISSTATEMENTS AT (UN) LUCKIN COFFEE INC. - Kukreja, Gagan (Indian Journal of Finance and Banking, 2021)
The research investigates alleged material misstatements in the financials of Luckin Coffee, a Chinese company listed in NASDAQ. The research is exploratory and based on publicly available information. The financial data has been obtained from their quarterly and annual reports submitted to Securities and Exchange Commission. The research shows the alleged corruption by inflating sales and profits by C-suite executives of the company. Nevertheless, before doing so, what failures in corporate governance led to this crisis? The admission of such material misstatements resulted in a massive loss to the investors and shaken the investment community’s trust once again. The research tried to determine what kind of audit procedures should have been implemented to earlier detection of fraud? What should have been done to protect stakeholders? What extra measures should the U.S. stock exchange take into consideration before listing foreign companies? What kind of ethical standards must be taught to the students/future executives to avoid such material misstatements? How can accounting bodies address such material misstatements? How can audit procedures be improved? This research will facilitate the policymakers, accounting and auditing regulators, board and various other stakeholders to deter, detect and mitigate such financial material misstatements and offers recommendations. JEL Classification Codes: M41, M42, M48, M148.